Effect of otago exercise on falls in patients with osteoarthritis: A protocol for systematic review and meta-analysis. Issue 50 (11th December 2020) - Xie, Chao; Wang, Weini; Pei, Jingfang; Wang, Haiyan; Lv, Honglin
Abstract: Background: Osteoarthritis (OA) is considered as an established risk factor for falls, while exercise can effectively prevent falls. However, whether otago exercise can prevent falls in OA patients is still controversial. Based on sufficient clinical studies, this study aimed to apply meta-analysis to evaluate the effectiveness of otago exercise on preventing falls in OA patients with. Methods: PubMed, EMbase, Web of Science and Cochrane Library were searched to collect randomized controlled trial (RCT) of the effect of Otago exercise on falls in OA patients. The search time limit was from the establishment of the database to September 2020. After the 2 researchers independently screened the literature, the data was extracted and the bias risk included in the study was evaluated. Meta-analysis was carried out with RevMan 5.3software. Results: The results of our meta-analysis could be published in peer-reviewed journals. Conclusion: This study provided high-quality evidence to support the effect of Otago exercise on falls in OA patients. OSF Registration number: DOI 10.17605/OSF.IO/Z5XGV.